2019
DOI: 10.26623/themessenger.v11i1a.821
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Factors for Building Brand Equity: Jordan Medical Tourism

Abstract: <p class="Default"><em><span lang="EN-MY">Building a brand with strong equity is a vital element for differentiation and competitiveness, especially in today’s highly competitive medical tourism. The literature indicated that Jordan has weak medical tourism brand equity. The contribution of customer relationship management and service quality in developing brand equity can’t be ignored. Studies on marketing activities towards building brand equity remain limited. Accordingly, 650 self-adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 42 publications
(51 reference statements)
0
9
0
1
Order By: Relevance
“…Three publications each were published in 2021, 2020, 2019, 2017, and 2015. The studies were conducted in different countries: Malaysia [ 6 , 19 ], South Korea [ 1 , 95 ], Iran [ 4 , 91 , 92 , 94 , 96 ], Indonesia [ 2 , 5 , 18 , 20 , 97 ], Kuwait [ 98 ], Jordan [ 93 , 99 , 100 , 101 ], India [ 9 , 17 , 23 , 26 , 89 , 102 ], Pakistan [ 90 ], Sri Lanka [ 103 ], Nairobi [ 104 ], and Vietnam [ 16 , 105 ]. Concentration of research is observed in developing countries, which can be explained by the desire for rapid development on the one hand, and the willingness to compare with highly developed countries on the other.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three publications each were published in 2021, 2020, 2019, 2017, and 2015. The studies were conducted in different countries: Malaysia [ 6 , 19 ], South Korea [ 1 , 95 ], Iran [ 4 , 91 , 92 , 94 , 96 ], Indonesia [ 2 , 5 , 18 , 20 , 97 ], Kuwait [ 98 ], Jordan [ 93 , 99 , 100 , 101 ], India [ 9 , 17 , 23 , 26 , 89 , 102 ], Pakistan [ 90 ], Sri Lanka [ 103 ], Nairobi [ 104 ], and Vietnam [ 16 , 105 ]. Concentration of research is observed in developing countries, which can be explained by the desire for rapid development on the one hand, and the willingness to compare with highly developed countries on the other.…”
Section: Resultsmentioning
confidence: 99%
“…Concentration of research is observed in developing countries, which can be explained by the desire for rapid development on the one hand, and the willingness to compare with highly developed countries on the other. The number of respondents varied significantly and ranged up to 100 people—in four studies [ 2 , 20 , 89 , 104 ], 101–250 people—in seven studies [ 5 , 19 , 23 , 92 , 97 , 98 , 103 ], 251–500 people—in sixteen studies [ 3 , 4 , 5 , 6 , 16 , 17 , 90 , 91 , 93 , 94 , 96 , 99 , 100 , 101 , 102 , 106 ], and over 501 people—in five studies [ 1 , 9 , 18 , 26 , 105 ]. Various methods of statistical analysis were used, including regression analysis [ 2 , 18 , 19 , 103 , 104 ], structural equation modeling (SEM)—in twenty-one studies [ 1 , 3 , 4 , 6 , 9 , 16 , 17 , 23 , 26 , 90 , 91 , 93 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(1) Knowledge management: Generating, disseminating, transforming, and utilizing information related to customers are the basic activities of knowledge management and strongly related to CRM (Akroush et al, 2010;Shriedeh, 2019). Knowledge management effectively supports knowledge from the customer about their tastes and needs; sharing of customer knowledge within different departments to facilitate concerted actions; and taking proper actions corresponding to the knowledge sharing (Sin et al, 2005).…”
Section: Customer Relationship Managementmentioning
confidence: 99%